AUTIS CENTER DENGAN PENDEKATAN HEALING ENVIRONMENT - Simbolon, Cory Glorya; Putro, Jawas Dwijo; Alhamdani, Muhammad Ridha (JMARS: Jurnal Mosaik Arsitektur, 2020)
Based on data from the Pontianak City Population and Civil Registry Office, the highest population growth rate after West Pontianak occurred in North Pontianak. The population growth is accompanied by an increasing number of cases of people with ASD. The handling of autism which has so far been carried out with the establishment of therapeutic sites such as the Technical Service Unit (UPT) Autis Center in West Pontianak, and Special School (SLB) with the closest distance Â± 14 km. As for other therapeutic sites in general is a function of the residence that still has distraction for people with ASD so that it is considered not sufficient enough. The supporting facilities available are deemed not fulfilling the needs of ASD in Pontianak, so there are still many cases of ASD sufferers who find it difficult to get expert treatment. For this reason, supporting facilities need to be held that can accommodate therapeutic activities in accordance with the character of persons with ASD.To design buildings that maximize the available environmental space and atmosphere program according to the type of needs and activities that are accommodated, the Healing Environment approach was chosen as the design solution for the Autis Center building. The Healing Environment approach is used to optimize the process of therapy, counseling, and education with an environment that can affect health through sensory and psychological patients with ASD.